Strategies of the Ulama in the Process of Islamization During Colonial Period in Nusantara - Amru, Moh Yusni; Alnizar, Fariz; Madjied, M Din (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2024)
This research focuses on the cultural strategies played by Indonesian ulama in the process of Islamization in the archipelago (Nusantara) during the colonial period. The cultural strategy built by Indonesian ulama is fundamentally inseparable from the seven elements of culture, namely knowledge, technology, economics, society, language, art, and religion. In this research, not all cultural elements are explained. Only the elements that were strategically directly used by ulama in Nusantara during the colonial period are explained. The method and concept of explanation is to explain the theory related to cultural elements according to experts, then contextualize it with the historical reality of Nusantara, especially the role of ulama in operating cultural elements as an Islamization strategy. Then, continued with relevant analysis, either as a conclusion or positioning it as an inspiration that gives birth to ideas. This research concludes that there are four cultural elements that were intensively played by Indonesian ulama in the Islamization process during the colonial period, namely the language system, political system, economic system, and knowledge system.